TPACK-informed online didactic design and self-regulated learning in distance education: A quasi-experimental study in a graduate statistics course - Kartono; Sudirman; Rodríguez-Nieto, Camilo Andrés (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to examine the effects of a TPACK-informed online tutorial design on self-regulated learning (SRL) achievement and improvement among graduate distance education students, while investigating whether prior mathematical knowledge (PMK) moderates those effects. Method: A quasi-experimental non-equivalent control group design was employed with 170 graduate students (experimental: n = 85; control: n = 85) enrolled in the Educational Statistics course (MPDR5202) at Universitas Terbuka. SRL was measured using a 37-item questionnaire across six dimensions (maximum score = 148). Data were analyzed using non-parametric statistics, specifically the Mann-Whitney U test and Kruskal-Wallis test. Findings: The TPACK-based tutorial design was associated with significantly higher SRL achievement (Z = −2.971, p = .003) and greater SRL improvement (Z = −4.807, p < .001) compared to the conventional tutorial design, though causal attribution is limited by the quasi-experimental design.PMK level alone did not produce a significant main effect on either SRL outcome. However, an omnibus rank-difference test across condition-by-PMK cells yielded a significant result (H = 25.762, p < .001), with post-hoc comparisons suggesting that students with medium and high PMK showed greater SRL improvement under TPACK-based instruction, while the pattern for low PMK students was inconclusive given the small subgroup size (n = 10). This interaction pattern should be regarded as preliminary. Significance: This study provides preliminary empirical support for the role of intentional, technology-integrated instructional design, specifically TPACK-informed online tutorials, in fostering self-regulated learning (SRL) in distance higher education, although causal conclusions remain limited by the quasi-experimental design. The finding that PMK appears to moderate the impact on SRL improvement suggests practical implications for instructional designers and distance educators. A uniform TPACK approach may be insufficient for students with low prior knowledge, pointing to the potential value of differentiated scaffolding strategies. However, this interaction pattern warrants replication in larger and more balanced samples before firm recommendations can be made.